From margins to mainstream : feminism and fictional modes in Italian women's writing, 1968-1990 - Lazzaro-Weis, Carol M., 1949- (Book collections on Project MUSE., 1993)
Carol Lazzaro-Weiss studies the fiction of twenty-five contemporary Italian women writers. Arguing for a notion of gender and genre, she runs counter to many Anglo-American and French feminist theorists who contend that traditional genres cannot readily serve as vehicles for feminist expression.